EVALUASI KELAYAKAN BISNIS PADA RUMAH PEMONDOKAN (KOST) MAHASISWA DI SEKITAR UNIVERSITAS MUHAMMADIYAH MALANG - Violetha, Hellen Mayora (Department of Management, 2014)
The purpose of the study is to evaluate the feasibility of students boarding house around University of Muhammadiyah Malang. The analytical tool are Net Present Value, Payback Period, Average Rate of Return, Internal Rate of Return, Profitability Index.The results of the analysis of boarding house owned by Mr. Rofiq show that the Net Present Value is 226.968.193,1 rupiahwhich is more than null (eligible). Value Payback Period is six years one month and seven days which is less than 20 years (feasible). Internal Rate of Return is 17,2063 % which is higher than COC, it is declared eligible.The value of Average Rate of Return is 43 % which is more than 15 % (feasible). The value of Profitability Index is 1,44 which is more than one (feasible).The results of the analysis of boarding house owned by Mrs. Atnah show that Net Present Value is 22.370.869,3 rupiah which is more than null, it is declared eligible. Value Payback Period is twelve years two months and twentythree days is less than 20 years (feasible). Internal Rate of Return is 17,8111 % which is higher than COC, it is declared eligible. The value of Average Rate of Return is 38 % which is more than 17 % (feasible). The value of Profitability Index is 1.058 which is more than one (feasible). In other words, the investments wasconducted by both the owner of boarding house was proceed.The results of the analysis of boarding house owned by Mr. Sofi show that Net Present Value is minus 170.035.625,2 rupiah which is not more than null (unfit). Value Payback Period is 32 years 2 months 12 days is more than 20 years (not feasible). The results of the value of the Internal Rate of Return is 3,7435 % is less than COC which is declared unfit. The value of Average Rate of Return is 2% which is not expected (less than 15%) declared unfit. The value Profitability Index is 0.32 which is less than one, it is declared unfit. Keywords:Net Present Value, Internal Rate of Return, Payback Period, Average Rate of Return, Profitability Index.